As God nie voed nie: Joël 1 in die konteks van wêreldhonger - Claassens, LJM; De Pere, WI (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
When God withholds food: Joel 1 in the context of world hunger A significant metaphor for God in the Old Testament is of God providing food (e.g. to Israel in Ex 16; Deut 8, as well as to all of creation Gen 1-2, Ps 104). But particularly in the prophetic literature, one finds the flipside of this image in the tragic descriptions of famine imagery. It is then that people may conclude that God sometimes fails to feed God’s people. This paper investigates the metaphor of God withholding food as it occurs in the book of Joel. In a quest to make sense of this problematic image for God, the paper reflects on the different ways in which the biblical traditions viewed famine. This biblical theological reflection on the metaphor of God withholding food is done in light of contemporary questions such as world famine and poverty.